The relationship between Body Mass Index (BMI) and Cesarean delivery rate - معافا, سارة; رجاء رجب,; أحمد حسن يوسف , (Latakia University Journal -Medical Sciences Series, 2022)
Background: Maternal Body Mass Index BMI has an impact on maternal and fetal pregnancy outcome . Thus, the incidence of CS increases. Aim:our aim of this study is to investigate the The relationship between Body Mass Index (BMI) and Cesarean delivery rate . Patients and Methods: A prospective cohort study included 101 pregnant women with a single life fetus. The pregnancy BMI was calculated and divided into 4 groups .Log-binomial regression analyses were performed to assess relative risk(RR) of CS between maternal BMI categories after exclusion of variables with a mediating effect . The duration of the research was one year from October 2020 to October 2021. Results: 3%,60.4%, 19.8% and 16.8% of the subjects were underweight, normal, over weight and obese respectively. Compared with women of normal BMI ,the risk of CSwas significantly increased in overweight and obese women(RR adj 3.4 95%CI(1.7-5.9). The obese group remained more likely to CS even after adjusting for prenatal and neonatal factors(RR adj 2.3 CI95%(1.2-3.1) Conclusion: Obese women are at a higher risk of having a CS and shouldtherefore be considered as a high risk and managed appropriately during pregnancy .